On-site PV characterization and the effect of soiling on their performance - Kalogirou, Soteris A.; Agathokleous, Rafaela; Panayiotou, Gregoris (My University, 2013)
This paper presents a study of the characteristics of three types of PV panels: monocrystalline, polycrystalline and amorphous silicon and the effects of soiling on their performance using on-site measurements. The total system consists of the three types of panels in pairs. Initially, the characterization of the PV panels is carried out to prove the similarity of the two pairs. Another test performed is the degradation of PV's performance under extreme soiling conditions caused by the artificial deposition of dust on the panels when their surface was dry and when it was wet before the dust deposition. The results showed that especially the artificial soiling on the wet PV surface presents a serious degradation of the PV performance. Finally, the effect of natural dust deposition on the panel's surfaces for a year is investigated. During this period a total of three dust episodes were recorded. These dust episodes concern the transfer of dust from the Sahara desert and these episodes usually end with a light rain which sticks the dust on exposed surfaces including PVs. Due to the exceptionally wet weather that we had during the testing period all episodes were followed by heavy rain, but even in this case a serious degradation of the performance of about 13% of the affected PV panels was recorded. The first finding of this study is that in winter the occasional rain is adequate to keep the PV surfaces clean whereas when a dust episode occurs, the panels should be cleaned manually. This is not the case for the summer time, which for Cyprus lasts for more than 8 months. The recommended cleaning is immediately after a dust episode and every 2-3 weeks in summer time according to how much loss the owner of the PV is willing to accept and the associated cleaning cost.
Keywords: Characterization; Dust; Performance; Photovoltaic; Soiling